Pengaruh Model Pembelajaran Problem Based Learning Bermuatan Media Massa terhadap Keterampilan Berpikir Kritis Peserta Didik Kelas V pada Mata Pelajaran IPAS di SDN Karangtanjung - Sari, Nur Indah Wulan; Lestari, Wahyu Maulida (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
The problem in this study stems from the low activity of students in learning, which is caused by one-way learning methods and less varied reading materials. This study aims to analyze the impact of the application of the Problem Based Learning (PBL) learning model combined with the latest mass media articles on the critical thinking skills of fifth-grade students of SDN Karangtanjung. This study uses a quantitative approach with a pre-experimental experimental method with a one-group pretest-posttest design. The population and sample in this study were all fifth-grade students of SDN Karangtanjung. The sampling technique used was nonprobability sampling with a total sampling type (saturated sample), namely all members of the population were used as research samples. The instrument used was a critical thinking skills test that had been validated by material experts and tested in the trial class. The results showed that the average pre-test score of 56.5 increased to 85.5 in the post-test. The paired sample t-test showed a significance value of 0.000 (<0.05), which means there was a significant difference between before and after the treatment. Thus, the implementation of a PBL model based on current media articles has proven effective in improving students' critical thinking skills in the science subject.